2018
DOI: 10.1016/j.neuropsychologia.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of functional fixedness during creative idea generation: An EEG study

Abstract: Decades of problem solving and creativity research have converged to show that the ability to generate new and useful ideas can be blocked or impeded by intuitive biases leading to mental fixations. The present study aimed at investigating the neural bases of the processes involved in overcoming fixation effects during creative idea generation. Using the AU task adapted for EEG recording, we examined whether participant's ability to provide original ideas was related to alpha power changes in both the frontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 58 publications
3
24
0
3
Order By: Relevance
“…Similar frontal alpha synchronization was reported by Camarda et al ( 2018 ), who observed a positive relationship between frontal alpha and the remoteness of the alternate uses generated by the participants who completed an alternate uses task. Interestingly, the authors split the time windows in the analysis and observed that participants who generated less original uses showed a decrease in frontal alpha synchronization over time, while participants who generated original uses maintained this synchronization over all the time windows analyzed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar frontal alpha synchronization was reported by Camarda et al ( 2018 ), who observed a positive relationship between frontal alpha and the remoteness of the alternate uses generated by the participants who completed an alternate uses task. Interestingly, the authors split the time windows in the analysis and observed that participants who generated less original uses showed a decrease in frontal alpha synchronization over time, while participants who generated original uses maintained this synchronization over all the time windows analyzed.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, the more original the generated use, the stronger the asymmetry of the observed effect was. Finally, Camarda et al ( 2018 ) linked alpha synchronization over the temporo-parietal sites (not lateralized) to the novelty of the generated responses, and interpreted it as related to internal semantic processing demands.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, is not always the case. The alpha frequency range has been reported to be involved with cortical excitation in the MFC in tasks involving creative processing and improvisation consistent with the conclusions of our study (Fink and Neubauer, 2008;Jauk et al, 2012;Benedek et al, 2014;Schwab et al, 2014;Lopata et al, 2017;Camarda et al, 2018;Lopata et al, 2017;Stevens and Zabelina, 2019). Furthermore, studies using fMRI and EEG have shown increased alpha synchronization in frontal and parietotemporal brain regions associated with brain activation during creative processing (Fink and Neubauer, 2008).…”
Section: Brain Related Activity Differentiating Improv and Scalesupporting
confidence: 89%
“…Taking together both RAT and visual originality results, we could speculate that the alpha power effect could reflect more internally oriented attention 53 , which may reflect selective inhibition of interfering external input 48,77,78 . This internally-directed attention could therefore facilitate the combination of remotely associated semantic information 25 and prevent functional fixedness during the creative ideation phase of creativity 79 . However, there are other possible explanations for the role of PPC, such as its role in efficient effective memory search and retrieval that could have a positive impact on these tasks 53 , working memory for object location 80 or spatial representation and updating 81 .…”
Section: Discussionmentioning
confidence: 99%